Socio-legal systems and implementation of the Nash solution in Debreu–Hurwicz equilibrium - Claus-Jochen Haake; Walter Trockel (Review of Economic Design, 2021)
In this article we combine Debreu's (Proc Natl Acad Sci 38(10):886–893, 1952) social system with Hurwicz's (Econ Design 1(1):1–14, 1994; Am Econ Rev 98(3):577–585, 2008) ideas of embedding a “desired” game form into a “natural” game form that includes all feasible behavior, even if it is “illegal” according to the desired form. For the resulting socio-legal system we extend Debreu's concepts of a social system and its social equilibria to a socio-legal system with its Debreu–Hurwicz equilibria. We build on a more general version of social equilibrium due to Shafer and Sonnenschein (J Math Econ 2(3):345–348, 1975) that also generalizes the dc-mechanism of Koray and Yildiz (J Econ Theory 176:479–502, 2018) which relates implementation via mechanisms with implementation via rights structures as introduced by Sertel (Designing rights: invisible hand theorems, covering and membership. Tech. rep. Mimeo, Bogazici University, 2001). In the second part we apply and illustrate these new concepts via an application in the narrow welfarist framework of two person cooperative bargaining. There we provide in a socio-legal system based on Nash's demand game an implementation of the Nash bargaining solution in Debreu–Hurwicz equilibrium.
Keywords: D02; C78; C72; 330; Socio-legal systems; Implementation; Social systems; Generalized games; Nash demand game